The client - Grisham, John. (new york : Bantam dell, 1993)
The client is eleven-year-old Mark Sway, who retained lawyer Reggie Love with a one-dollar bill. The reason Mark needs a lawyer is the same reason his eight-year-old brother is comatose in the hospital from shock -- they witnessed a suicide. The victim was a lawyer and unfortunately he told Mark something before he died -- something the police, the FBI, and the mafia are very interested in. Strong language and some violence. Bestseller 1993.
All Ages.
Keywords: Mafia -- Fiction; Suspense; New Orleans (La.) -- Fiction; Legal stories